Contra caecitatem iudeorum: el tópico de la ceguera de los judíos en la plástica medieval hispánica - Rodríguez Barral, Paulino (’Ilu. Revista de Ciencias de las Religiones, 2007)
The topos of jews’ blindness, recurrent in adversos iudaeos literature, embodies in the image of blindfold Synagoga in medieval visual arts. The first part of this paper focuses on its integration in different contexts of medieval Spanish art. Diferent, but not less interesting, is the way caecitatis iudeorum is illustrated in some illuminated manuscripts of Breviari d’Amor by Matfre Ermengaud and Fortalitium Fidei by Alonso de Espina, also subject of study throughout these pages.